Rancang Bangun Aplikasi Service pada PT. Indo Bismar Komputer - Perdana, Gemilang Citra; Arifin, Mochammad; Erstiawan, Martinus Sony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT. Indo Bismar Komputer is a distributor company of computer devices which sells and services computer spareparts. On service section especially on service administration section have some problems in receiving service device record that wrote directly into paper manually which caused data redundancy. Other problem is service administration did confirm to customer about customer's device status only based on service administration's memory that cause customer's device overstacked on service section, slower service response, unsatisfied customer, lack of customer trust, services income isn't optimal, inaccurate reports from not fixed service fee.Based on problems that faced on administration service staff, a solution for those problems is making an application for PT. Indo Bismar Komputer which used for computer spareparts sales, measures and monitoring how much technician’s income from services.Main purpose of this research application is generating an output into services income tech report which used to measure how much tech income, overall services income report, services transaction report and spare parts selling report with income target within periods which have decided by the owner of PT. Indo Bismar Komputer.Keyword: System, Service, Payment, Sales, Application